PgUGT95B2 preferentially metabolizes flavones/flavonols and has evolved independently from flavone/flavonol UGTs identified in Arabidopsis thaliana. (January 2019) - Wilson, Alexander E.; Wu, Sheng; Tian, Li
Abstract: UDP-dependent glycosyltransferases (UGTs) convert aglycones into more stable, bioactive, and structurally diverse glycosylated derivatives. Pomegranate ( Punica granatum L.) produces various glycosylated phenolic metabolites, e.g. hydrolyzable tannins (HTs), anthocyanins, and flavonoids, and constitutes an excellent system for investigating the corresponding UGT activities. Here we report the cloning and functional characterization of a pomegranate UGT, Pg UGT95B2, which is highly active towards flavones and flavonols and can glycosylate at more than one position in the substrate molecule. Particularly, Pg UGT95B2 has the strongest activity towards tricetin (flavone with a tri-hydroxylated B-ring) and can act at the 4'- O position of its B-ring. In addition, Pg UGT95B2 was able to glycosylate flavones present in pomegranate metabolite extracts. Conversely, Pg UGT95B2 did not produce a galloylglucose ester (precursor for HT biosynthesis) or anthocyanins in enzyme assays. Our phylogenetic analysis suggested an independent evolution of Pg UGT95B2 and flavone/flavonol UGTs identified in the model plant Arabidopsis thaliana through convergent evolution or gene loss. Graphical abstract: Image 1 Highlights: Pomegranate produces diverse glycosides and is a good system for studying UGTs. Pg UGT95B2, a pomegranate UGT, preferentially metabolizes flavones and flavonols. Pg UGT95B2 glycosylates flavones present in pomegranate metabolite extracts. Pg UGT95B2 has evolved independently from flavone/flavonol UGTs in Arabidopsis. The Pg UGT95B2 clade represents a distinct group in plant UGT phylogeny.